Pengaruh Hedonic Shopping Motivation dan Shopping Lifestyle terhadap Impulse Buying Pelanggan E-Commerce Shopee Member Platinum di Daerah Sumenep - Fatihatul Fitriyah; Tajus Subqi (Al-Musthofa: Journal of Sharia Economics, 2023)
This study uses quantitative research, the aim is to determine the influence of Hedonic shopping motivation and Shopping lifestyle on Impulse Buying E-Commerce Shopee Member Platinum customers. The method used in this research is descriptive method based on purposive sampling technique with 117 respondents active users in E-commerce shopee who have reached platinum level. The primary data and secondary data used were sourced from distributing questionnaire data and obtained from literature from various sources. Meanwhile, for testing techniques and data analysis using the SPSS 22 for Windows application. The results of this study indicate that the variables Hedonic Shopping Motivation and Shopping Lifestyle simultaneously and partially have a positive and significant effect on Impulse Buying.